PENGARUH VARIASI SUDUT UJUNG MATA POTONG KARBIDA TERHADAP KEKASARAN DAN TOPOGRAFI PERMUKAAN LOGAM Al 6061 PADA PROSES PEMBUBUTAN - Sobron Lubis; Rosehan Rosehan; Rico Wiguna (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Abstract: In the process of metal cutting, cutting tools is an important factor to consider. Selection of cutting parameters and cutting tools geometry contributes to the surface condition of the resulting workpiece, especially surface roughness. The nose radius of cutting tools is a piece that rubs against the workpiece that will form a scratch to produce a flake. Various types of cutting tools angles today are developed and certainly give effect to changes in surface roughness of the workpiece and topography. To know the condition of surface workpiece produced, then conducted research influence variation tool nose radius cutting tools to roughness and topography surface workpiece. This research was conducted using CNC lathe. Three variations of end of carbide insert tip used i.e. 0.4, 0.8, and 1.2 mm are installed. Right on tool holder cutting tools. The cutting speed used is 500 m / min, depth of cut 0.2 mm, and feeding of 0.3 mm / put. Material workpiece aluminum alloy type 6061 turning without using coolant. The workpiece of the lathe result is measurement of surface roughness by using Mitutoyo surface test, and observation of workpiece surface condition done by Jenco digital microscope model BC 4-311. The result of the analysis shows that the surface roughness value is inversely proportional to the increase of nose radius cutting tools tool. The larger the nose radius cutting tools, the smaller the surface roughness. The lowest roughness value is 1.046 μm with cutting speed of 500 m / min and 1.2 mm tool nose radius cutting tools. The percentage decrease in surface roughness with the difference of nose radius cutting tools tool is 12.24%.